Fast inverse elastic scattering of multiple particles in three dimensions*The first author was partially supported by the Funds for Creative Research Groups of NSFC (No. 11621101), NSFC Grants 11871427 and U21A20425. (1st October 2022) - Lai, Jun; Zhang, Jinrui
Abstract: Many applications require recovering the geometric information of multiple elastic particles based on the scattering information. In this paper, we consider the inverse time-harmonic elastic scattering of multiple rigid particles in three dimensions. We measure the far field information and apply the time reversal method to recover the unknown elastic particles. Two regimes are considered depending on the size and distance among particles. First, an asymptotic analysis for the imaging of small and distant particles is given based on the scattering property of a single particle, which can be used for selective focusing. Second, when particles are not small but well-separated, a fast algorithm, based on the combination of multiple scattering theory and fast multipole method, is proposed to efficiently simulate the forward multiple scattering problem and applied to the inverse elastic scattering. Numerical experiments demonstrate the proposed method can effectively recover the locations and shapes of multiple unknown particles.